Design of Groundwater Extraction in Open Cut Foundation Pit and Simplified Calculation of Ground Subsidence due to Dewatering in Sandy Pebble Soil Strata. (27th January 2020) - Zhang, Lu; Zhou, Xiaojun; Pan, Yingdong; Zeng, Bowen; Zhu, Dongfeng; Jiang, Huaizu
Abstract : In order to study the design of incomplete well point for groundwater extraction in open cut foundation pit in which the inner and outer aquifers are not completely isolated and the change mechanism of ground subsidence due to dewatering in the foundation pit, an open cut foundation pit for a subway station on Chengdu Metro Line 6 is taken as an example; meanwhile, the typical sandy pebble soil strata are also considered as a research object in this paper. Firstly, a new method for designing groundwater extraction in the open cut foundation pit is presented and applied to the practical project. The dewatering funnel curve is derived based on Dupuit's assumption, and the ground subsidence around the foundation pit due to groundwater extraction is calculated using the stratification summation method as well as considering the effect of seepage force. The finite difference software FLAC 3D is employed to simulate the groundwater extraction process in the foundation pit, and the simulation of groundwater extraction by single well point and group well points is also carried out and the unapparent effect of group well points is obtained. The comparison among on-site monitoring, theoretical calculation, and numerical simulation shows that these values have the same trend in indicating ground subsidence, and the conventional stratification summation method is conservative, and the algorithm considering the effect of seepage force is more accurate. Therefore, the ground subsidence curve caused by groundwater extraction in the foundation pit is presented. The above research methods and results can be applicable for practical engineering and be used to guide the design and construction of groundwater extraction in the foundation pit by using the open cut method in sandy pebble soil strata.